Gender Discrimination in Orhan Pamuk's 'Snow' and Khaled Hosseini's 'A Thousand Splendid Suns' - Iis Sugianti (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2018)
Women's life without discrimination or violence is the freedom and entitlement of women's rights. The objective of the study is to achieve the idea. Dealing with it, the researcher applies feminism approach proposed by Damewood's theory of gender discrimination. Gender discrimination refers to the practice of granting or denying rights or privilege to a person based on his/her gender that is longstanding and acceptable to both genders. The novel `Snow` and `A Thousand Splendid Suns` focus on gender discrimination, violence, oppression, and struggle to fight against them. The researcher explores how gender discrimination, patriarchy culture and most of violence and oppression happened in family and country. The phenomenon of violence is not only a discrimination done by husbands who do gender discrimination in family, but also a fight done by a wife to fight against them, it depends on its case. In `Snow`, the women character faced many problems related to their headscarves. They are discriminated by their government and parents. Kadife is depicted as a brave woman. She tries to defend women‟s right in Kars to keep on using their headscarves. While in A `Thousand Splendid Suns`, the limitation of women`s activity happened. Women are banned to get education and they should stay at home. Mariam and Laila get oppression and violence by their husband. Their struggle is shown in the murder of their husband, Rasheed. The unstable practice of gender discrimination was continuously preserved by the culture, not religion. It was like a patriarchal culture that is one of clear examples of the women phenomena in the world and it can be in the form of prohibition and limitation of the role of women in the public area.